(untitled) (Research, Society and Development, 2022)
In addition to the intense income inequality in Brazil, the country still has a critical discrepancy between regions. Given this scenario, the objective of this work was to verify how income inequality and the level of per capita income were related in the Northeast Region, for the years 1991, 2000 to 2010, in light of the hypotheses of Kuznets and N. For this, Data were used in a panel with annual frequency for the 26 Brazilian federation units and the Federal District. It was analyzed whether the relations between inequality indicators and economic growth would have the format of an "inverted U" as it defends the hypothesis of Kuznets or the format next to an N. It was employed the income in cubic level as they defend more modern works that challenge the theory of Kuznets. In the estimates for the Northeast Region, the coefficients associated with the third-degree polynomial of per capita income are significant and with the signs predicted to consolidate the hypothesis of N. It can-it is inferred, then, that growth at a certain stage can even reduce social inequalities, but these tend to increase again.